Evaluasi Efek Inflasi dan Perubahan Suku Bunga terhadap Performa Saham PT Indofood Sukses Makmur Tbk di Bursa Efek Indonesia (2020-2022) - Dharmayanti, Dewi Sari; Suparta, I Nyoman; Ardiansyah, Wisnu (Universitas Pahlawan Tuanku Tambusai, 2024)
The study is to evaluate the effects of interest rates and inflation on the stock performance of PT Indofood Sukses Makmur Tbk, a company listed on the Indonesia Stock Exchange (BEI), from 2020 to 2022. A quantitative methodology combined with a descriptive approach is used to perform the research. The subject of discussion is (ICBP) and PT Indofood Sukses Makmur Tbk (INDF), which is the company's parent. The sample consists of both firms' financial reports for the given time that were retrieved from the IDX. The data gathering method uses a purposive sample strategy that is dependent on secondary data sources. The results show that, with a significance value of 0.143 (higher than 0.05) and a t-value of -1.491 (smaller than the t-table value of 2.015), inflation (X1) has a negative impact on (Y). X2 have a negative impact on stock performance (Y), as shown by the t-value of -1.509 (smaller than the t-table value of 2.015) and the significance value of 0.139 (more than 0.05). Nonetheless, as indicated by a computed F-value of 2.95, which is higher than the F-table value of 2.82, inflation (X1) and interest rates (X2) taken together have a substantial impact on stock performance (Y).